URBANIZATION, ENVIRONMENTAL PLANNING AND MANAGEMENT: A CHALLENGE FOR JAMAICA - Leiska J., Powell (PLANNING MALAYSIA, 2009)
The rapid pace of urbanization has presented numerous challenges for developing countries such as Jamaica. The effects of urbanization coupled with poor environmental and development practices have exerted tremendous pressure on the country’s fragile and limited natural resources. This issue is exacerbated by poverty, poor urban planning and management and lack of enforcement of existing land use regulations. The purpose of this paper is to critically examine the challenges in reversing negative environmental trends and practices which is increasing the vulnerability of the population, economy, infrastructure and other vulnerable elements of the society to the devastating impacts of natural hazards. The growing threats from hurricanes and tropical storms has have occurred over the last 10 years have highlighted the need for more sustainable developtnent. The report concludes with a number of recommendations that are critical to address the never ending cycle of environmental degradation.